Pemahaman dan Minat Berinvestasi di Pasar Modal Mahasiswa PTKIN dan PTKIS di Sumatera Barat (Sebuah Penelitian Metode Mixed) - Gina Havieza Elmizan; Vera Rahmawati; Anisa Talim (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2022)
Sharia investment is currently trending in the world of investment in Indonesia. Moreover, the current PTKI students are Generation Z, who are more familiar with the virtual world and the world of online investment. Thus, the understanding and interest of Generation Z in sharia investment needs to be analyzed in order to develop the Islamic capital market. The research article explains how high the understanding and interest of public and private Islamic university students towards Islamic capital market investment is. It uses a combination of quantitative and qualitative methods. Quantitative research is done by survey using Google Form, to 300 students at PTKIN/S in West Sumatra. The samples are 154 student respondents from 3 PTKIN and 129 students from 5 PTKIS. The effect of understanding on interest in investing in the Islamic capital market is significant. If understanding increases by 1 point, then interest will increase by 0.481 points. There is no difference in the investment interest of PTKIN students and PTKIS students. Qualitative research was conducted by collecting student arguments in FGDs related to the determinants and efforts to increase understanding and interest in investing in the Islamic capital market. Many determinants of understanding come from external, while interest is heavily influenced by internal factors. Efforts to increase understanding can be done by studying academically, using the internet more wisely, and attending seminars and discussions. Meanwhile, increasing interest, it can be done by increasing understanding, motivation, and interaction with Islamic capital market investment figures.